Adverse pregnancy outcomes among pregnant women living with HIV in Hubei province, China: prevalence and risk factors. Issue 3 (4th March 2023) - Wu, Mengmeng; Yan, Yajun; Zou, Shi; Wu, Songjie; Feng, Ling; Liu, Yanbin; Guo, Wei; Tang, Weiming; Liang, Ke
ABSTRACT: Mother-to-child transmission of Human Immunodeficiency Virus (HIV) has been greatly reduced with the advance of intervention technology. However, adverse pregnancy outcomes (APOs) are still common, and little is known about the driving forces of APOs among pregnant women living with HIV in China. Between January 2004 and December 2020, a total of 638 pregnancies among pregnant women living with HIV were enrolled in this study, 84 (13.2%) pregnancies with 87 APOs were reported. Preterm birth (3.8%), ectopic pregnancy (3.4%), spontaneous abortion (2.0%), and embryo arrest (1.7%) were the most common APOs in pregnant women living with HIV. Exposure to antiretroviral drugs (ARVs) during the first trimester (RR = 4.077, 95% CI: 0.521, 1.484, P<0.001) and the first CD4+ T lymphocyte count (CD4 count)≤ 350/μl (RR = 2.227, 95% CI: 0.063, 0.991, P = 0.026) were risk factors of APOs. The age≤ 30 years (RR = −2.513, 95% CI: −1.067, −0.132, P = 0.012) was associated with the decreasing of APOs. Encouraging people to initiate combination antiretroviral therapy and reach a high CD4 count level before pregnancy would be helpful to prevent APOs. Pregnant women exposed to ARVs in the first trimester needed more attention for APOs.